Green synthesis of ag nanoparticles for water treatment (antimicrobial on Eschirichia coli) - Mazlina Mat Darus (N/A, 2017)
Green synthesis of ag nanoparticles for water treatment (antimicrobial on Eschirichia coli) by Mazlina Mat Darus